2004
DOI: 10.1172/jci22422
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mediators of hepatic steatosis and liver injury

Abstract: Obesity and its associated comorbidities are among the most prevalent and challenging conditions confronting the medical profession in the 21st century. A major metabolic consequence of obesity is insulin resistance, which is strongly associated with the deposition of triglycerides in the liver. Hepatic steatosis can either be a benign, noninflammatory condition that appears to have no adverse sequelae or can be associated with steatohepatitis: a condition that can result in end-stage liver disease, accounting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
721
1
27

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 973 publications
(775 citation statements)
references
References 88 publications
26
721
1
27
Order By: Relevance
“…All these features are named collectively NAFLD [3]. Observed only in the HFD and HFHF groups, ballooned hepatocytes are delimited to the most severe form of hepatic injury and indicate cell necrosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…All these features are named collectively NAFLD [3]. Observed only in the HFD and HFHF groups, ballooned hepatocytes are delimited to the most severe form of hepatic injury and indicate cell necrosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…Инсулин стимулирует поглощение клетками глюкозы, активируя экспрессию и выставление на плазматическую мембрану дополни-тельного количества глюкозных транспортеров ГЛЮТ4. Одновременно этот гормон индуцирует экспрессию ферментов липогенеза: ацетил-КоА-карбоксилазу, синтазу ЖК и пальмитоил-КоА-элонгазу [4] и стеарил-КоА-десатуразу [5]. Последние два фермента удлиняют пальмитиновую насыщенную ЖК (НЖК) на молекулу ацетил-КоА (на 2 атома углерода) с образованием С18:0 стеариновой ЖК [6].…”
Section: инсулин и оптимизация In Vivo субстратов для наработки энергииunclassified
“…The ability of the liver to process fatty acids and transport lipids to other tissues is affected by toxins, diet and drugs [26][27][28][29][30][31][32][33][34]. Previously, we have shown that exposure to THS toxins results in lipid accumulation in hepatocytes of exposed mice.…”
Section: Introductionmentioning
confidence: 99%